The Goal Programming Method: Minimizing Expenses and Maximizing Assets for Optimizing the Financial Statements of Bank Syariah Indonesia - Pradjaningsih, Agustina; Sukma Lailatul Fadillah; Riski, Abduh (RANGE: Jurnal Pendidikan Matematika, 2025)
Every company, including banks, prepares financial reports as a source of information regarding a company's performance and financial position. Economic reports have five essential elements: assets, liabilities, equity, income, and expenses. Each bank has several goals; to achieve the goal, a method is needed that can solve problems with several objectives.  This study aims to apply the Goal Programming (GP) method to solve several financial goals simultaneously and analyze solutions to optimize financial reports at Bank Syariah Indonesia (BSI). Goal Programming is a multi-objective optimization technique that allows decision-makers to balance conflicting goals by prioritizing deviations from predetermined targets. This study uses GP to model BSI's financial constraints and objectives: maximizing assets, minimizing liabilities, maximizing equity, maximizing income, and minimizing expenses. The solution for the GP model is calculated using Lingo software. So far, BSI has never used the Goal Programming Method to optimize financial statements, offering a new analytical framework for the bank's decision-making process.he study results show that Bank BSI's financial reports for 2019 to 2022 have been optimal by implementing the GP method and the assistance of Lingo software. This is indicated by all deviations being successfully minimized and achieving the target. The minimized expenses are IDR 68.012.380 million, and the maximized assets are IDR 1.018.471.648 million.